Nail‐plate dystrophy of the fifth toenail: thinking outside the box. (24th November 2020) - Dika, E.; Lambertini, M.; Misciali, C.; Fanti, P. A.; Contedini, F.; Pinto, V.; Pignatti, M.; Cipriani, F.; Corti, B.; Piraccini, B. M.
Abstract : Click here for the corresponding questions to this CME article.